2020
DOI: 10.1017/jgc.2020.14
|View full text |Cite
|
Sign up to set email alerts
|

How school counsellors cope with suicide attempts among adolescents — A qualitative study in Israel

Abstract: The aim of the study was to examine how school counsellors cope with suicide attempts among students in their schools. A qualitative phenomenological methodology was used. Participants included 24 Israeli high school counsellors aged 32–62. All interviews were recorded, transcribed, and analysed thematically. The findings indicate that counsellors find students’ suicide attempts difficult, disconcerting, painful and confusing to manage, and note the complex nature of their dealings with the adolescents, their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The capacity of clinicians to identify signs of potential suicide is paramount for the administration of proper crisis management and suicide intervention tactics, particularly during times of severe crisis [ 28 ]. Given the seriousness of the issue, a substantial commitment toward evaluating suicide risk is vital [ 29 - 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of clinicians to identify signs of potential suicide is paramount for the administration of proper crisis management and suicide intervention tactics, particularly during times of severe crisis [ 28 ]. Given the seriousness of the issue, a substantial commitment toward evaluating suicide risk is vital [ 29 - 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contending with various events in the field of counselling is challenging and forces counsellors to adopt mechanisms for coping with the weighty emotions and thoughts that can sometimes overflow into their personal lives. Their strategy seems to be to maintain emotional distance from certain events and from difficult students (Levkovich & Elyoseph, 2023; Levkovich & Vogdor, 2021). The current study revealed that school counsellors often avoid engaging in intense one‐on‐one conversations with foster children about their experiences.…”
Section: Discussionmentioning
confidence: 99%
“…The literature points to a high rate of exposure to trauma among children who have been in foster care (Kaasboll et al, 2019; Salazar et al, 2013). A recent study suggested that school counsellors should receive proper professional training on the topic of trauma (Levkovich & Ne'emani, 2022; Levkovich & Vigdor, 2020). Such training can enable them to develop a comprehensive counselling program for identifying, assessing and treating f students with post‐trauma (Martinez Jr et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, only some of the teachers in the current study received support and guidance from the local school counselor and none of them received help from SHEFI. Clearly the teachers' unfamiliarity with the topic of mourning and loss and their lack of outside support make it difficult for them to provide effective responses to bereaved students (; Levkovich, & Vigdor, 2020;Busu & Luchici, 2016;Lane et al, 2014). This may also explain the teachers' sense of inadequacy and confusion.…”
Section: Discussionmentioning
confidence: 99%